Analisis Laporan Keuangan pada Perusahaan Jasa PT Pengembangan Investasi Riau (International Forum of Researchers and Lecturers, 2024)
The purpose of this research is to find out and analyze how the percentage of completion method is applied in recognizing construction income applied by PT. Housing Development (Persero). The method used in this research is descriptive qualitative. The type of data used is primary data from interviews with the company regarding revenue recognition and secondary data in the form of PT financial data. Housing development, especially the Juanda Business Center project, Pager Hamlet, Saworatap, Kec. Gedangan, Sidoarjo Regency. The results of research carried out by the company in applying the percentage of completion method use a physical approach which is calculated based on estimates of physical progress alone without taking into account the costs that have been incurred in completing the project.